Information and Communication Technology (ICT) Literacy and Application Skills Among K to 3 Teachers - Maliones, Janice (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the Information and Communication Technology (ICT) literacy and application skills of K-to-3 teachers and explored the relationship between these competencies to inform targeted interventions. Anchored on the National ICT Competency Standard Framework (NICSF), the study employed a descriptive correlational research design. Data were collected from 30 K-to-3 teachers in public elementary schools using a researcher-developed questionnaire measuring ICT literacy and application across key areas such as word processing, spreadsheets, presentation tools, and pedagogical integration. Data analysis utilized weighted mean, Pearson Product-Moment Correlation, and t-test. Findings revealed that teachers exhibited a slightly literate level of ICT literacy (mean = 2.48) but a highly applied level of ICT application skills (mean = 3.57), indicating a gap between theoretical knowledge and actual practice. A strong positive correlation (r = 0.68, p = 0.001) was found between ICT literacy and application skills, confirming that higher literacy is associated with improved classroom application. The study also highlighted variability in pedagogical integration despite consistent use of basic ICT tools. The study concluded that K-to-3 teachers are practitioner-oriented users of ICT, demonstrating adaptability despite limited formal literacy. It recommends the implementation of targeted ICT enhancement training programs focusing on advanced technical skills and pedagogical integration, along with peer mentoring and expanded research scope. This study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) by promoting teacher digital competence and effective technology integration in education. It contributes to educational, technological, and institutional sustainability by strengthening teacher capacity, improving instructional quality, and supporting policy and training development for a future-ready education system.